Strategies for Cultivating Healthy Workplaces in the IT Industry: A Comprehensive Examination of HR Dynamics - N V, Manoj Kumara; K R, Nithyashree (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Background: In modern society, the IT sector plays a pivotal role in driving innovation, connectivity, and efficiency across various industries. In the fast-paced landscape of the Information Technology (IT) industry, the pursuit of strategies to foster healthy workplaces is a critical imperative. Aims: This research aims to examine the impact of workplace stress on employee productivity and mental well-being in the Information Technology (IT) industry, specifically focusing on companies in Mysuru city. It also seeks to propose and evaluate strategies for creating a healthy workplace environment within this sector. Research Methodology: The study adopts a descriptive research approach, conducting a comprehensive literature review to understand existing theories and practices related to building healthy workplaces in the IT industry. Simple random sampling is employed to select 150 IT employees from 6 major IT companies in Mysuru city. Data is collected using a structured questionnaire and analyzed using descriptive statistics, ANOVA, and a 5-point Likert scale to unravel patterns, trends, and variations in workplace dynamics. Additionally, company-wise analysis is conducted to assess the impact of various workplace strategies. Results: The findings indicate that workload intensity remains consistent across age groups, and there are no significant gender-based disparities in various workplace stressors. However, flexible work arrangements and mental health programs exhibit significant variations among companies, highlighting the need for tailored wellness initiatives. Age-neutral and gender-inclusive strategies are recommended to foster a healthier work environment. Conclusion: This research underscores the importance of addressing workplace stress in the IT industry and emphasizes the need for customized wellness initiatives tailored to the unique dynamics of each organization. Moving forward, future research could explore the effectiveness of specific interventions to provide actionable guidelines for enhancing employee well-being and productivity in the evolving IT industry.